Analisis Tingkat Technopreneurship Pada UMKM Sambel Pecel Wahyu Tumurun Kota Madiun - Ramadhan, Dyan, Suci (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2018)
Madiun city is one of the cities located in the East Java region that has a typical foodthat is "Sambel Pecel". One of the most famous pecel sambel in Madiun City is sambel pecelWahyu Tumurun. UMKM sambel pecel Wahyu Tumurun is one of the excellent products ofMadiun city. There needs to be a technopreneursip level analysis at UMKM sambel pecelWahyu Tumurun of Madiun City in order to improve the results and the quality developmentof the undertakings, so as to be able to compete in the global market. The research wasconducted by using qualitative descriptive research method. Data collection technique isdone by observation, interview, and documentation. Analysis of data used with the process ofdata collection, data reduction, data presentation, and conclusion. From the research resultlevel Technopreneurship of UMKM Sambel Pecel Wahyu Tumurun at level 5 and level 4. Atlevel 5 includes appropriate technology assistance, documentation of production process,introduction of alternative process technology, introduction of market expansion andimprovement of business efficiency and productivity, assistance to improve new technologyaccess capability, utilization of technology in product design / design process, improvementof innovation climate among staff. At level 4 includes funding of technology utilization,technology audit, mentoring and training on UMKM is more emphasized on improvement ofproduct research and development capability.